Field notes contributed by Robert K. Myers, fall 1984 - Myers, Robert K.et al (1984)
Field notes were contributed by Robert K. Myers, fall 1984. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1984. Epson - sheet feed